Ehealth education for future clinical health professionals: An integrated analysis of Australian expectations and challenges - Dattakumar, A.; Gray, K.; Maeder, A.; Butler-Henderson, Kerryn (IOS Press, 2013)
Australia is experiencing challenges in its health workforce profile to embrace reforms based on ehealth. Although there is much literature on the importance of ehealth education, our study shows that ehealth education for entry-level clinicians is not meeting the demands for a technologically savvy clinical health workforce. This poster reports on a nationally funded project. Support for this project has been provided by the Australian Government Office for Learning and Teaching. The views in this project do not necessarily reflect the views of the Australian Government Office for Learning and Teaching, which examines ehealth education for the future clinical workforce in Australia. It discusses 3 key components: the current state of teaching, learning and assessment of ehealth education in health profession degrees in Australia; inclusion of ehealth competencies in accreditation guidelines of health profession degrees and ehealth skills and competencies in job descriptions for the future Australian clinical workforce. It is based on a systems view methodology that these three components are interrelated and influence the development of an ehealth capable health workforce. Results highlight that further research and development across the health workforce is needed before the education of future clinical health professionals can keep pace with the changes that ehealth is bringing to the Australian healthcare system.